OCCURRENCE OF LUMPY SKIN DISEASE IN CATTLE IN THE WORLD - V. P. Semakina; M. V. Zhiltsova; A. V. Savvin; T. P. Akimova (Ветеринария сегодня)
Lumpy skin disease is a viral highly contagious emerging transboundary disease of cattle. The incubation period of lumpy skin disease lasts for 28 days. Virus is transmitted through skin, mucous membranes of respiratory, digestive organs and conjunctiva, then it enters into the lymph nodes where it replicates, and then it is transported along the body with blood. Animals excrete the virus with expired air, saliva, semen, milk, nasal and ocular discharges, and exudates. The first reported outbreak of lumpy skin disease occurred in Central Africa, Zambia, in 1929. Then the disease was reported in the northern part of the continent. In the last years lumpy skin disease tends to spread to the north-east and north-west from the historical areal of the virus. Rapid disease spread is observed in the countries of Middle East, Central Asia and European Union. From July 2012 to July 2016 the disease affected 18 countries and became spread in the Middle East and moved to the north. In 2015 the first reported outbreak of lumpy skin disease occurred in the territory of the Russian Federation. It became widely spread in the south of Russia. Lumpy skin disease spread in the territory of Turkey, Armenia and Azerbaijan pose a threat to the Russian Federation. The prevention of further disease spread in Asia and Europe require cooperation of veterinary specialists and international authorities.